2009
DOI: 10.1088/0004-637x/699/2/1938
|View full text |Cite
|
Sign up to set email alerts
|

Biases on Initial Mass Function Determinations. Iii. Cluster Masses Derived From Unresolved Photometry

Abstract: It is currently common to use spatially unresolved multifilter broadband photometry to determine the masses of individual stellar clusters (and hence the cluster mass function, CMF). I analyze the stochastic effects introduced by the sampling of the stellar initial mass function (SIMF) in the derivation of the individual masses and the CMF, and I establish that such effects are the largest contributor to the observational uncertainties. An analytical solution, valid in the limit where uncertainties are small, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 67 publications
(94 reference statements)
0
22
0
Order By: Relevance
“…The scatter on the redder side can be understood in terms of interstellar reddening. On the other hand, the blueward shift of the distribution with respect to the colour expected for the 10–300 Myr SSP could be due to the stochastic sampling of the stellar IMF that affects the colours of low‐mass clusters (Cerviño & Luridiana 2004; Maiz‐Apellaniz 2009). Hence, the presence of many clusters bluer than B − I <0.5 mag suggests that majority of the clusters has mass of <10 4 M.…”
Section: Discussionmentioning
confidence: 99%
“…The scatter on the redder side can be understood in terms of interstellar reddening. On the other hand, the blueward shift of the distribution with respect to the colour expected for the 10–300 Myr SSP could be due to the stochastic sampling of the stellar IMF that affects the colours of low‐mass clusters (Cerviño & Luridiana 2004; Maiz‐Apellaniz 2009). Hence, the presence of many clusters bluer than B − I <0.5 mag suggests that majority of the clusters has mass of <10 4 M.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Uneven IMF sampling in less massive clusters can also affect the expected NIR flux. Studies of the evolution of the stellar isochrones (Maíz Apellániz 2009, among many others) have shown that red supergiants (RSGs) dominate the SC light in red and near‐IR wavelengths as early as 6 Myr. Z01 models are constructed by integrating the contribution to the cluster's light from all the stars populating a well‐sampled IMF, normalized with respect to the mass of the cluster.…”
Section: What Is the Cause Of The Red Excess?mentioning
confidence: 99%
“…However, standard SSP models assume a continuously populated stellar initial mass function (SIMF), while clusters consist of a finite number of stars. For unresolved clusters, the random sampling of the SIMF can strongly affect integrated properties such as cluster colors, magnitudes, and parameters (ages, masses) derived from them (Cerviño & Luridiana 2006;Maíz Apellániz 2009;Popescu & Hanson 2010a,b). A promising attempt to take the stochastic color fluctuations into account when deriving ages and masses has been made by Fouesneau & Lançon (2010), based on a Bayesian approach.…”
Section: Aperture Correctionsmentioning
confidence: 99%